The Comparison of Medical Terms in English and Uzbek Languages - Akhmatova Mahfuza Dilshоd kizi (Periodica Journal, 2023)
This article provides a comparison of medical terms in English and Uzbek languages. The study is conducted using a comparative analysis approach to identify similarities and differences in the two languages. The article presents the methods used to collect data, the results of the study, and a discussion of the findings. The conclusion provides insights into the importance of language proficiency for medical professionals and suggests areas for future research.
Keywords: terms; English; Uzbek